2011
DOI: 10.1016/j.neuroimage.2010.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Phasic and sustained fear in humans elicits distinct patterns of brain activity

Abstract: Aversive events are typically more debilitating when they occur unpredictably than predictably. Studies in humans and animals indicate that predictable and unpredictable aversive events can induce phasic and sustained fear, respectively. Research in rodents suggests that anatomically related but distinct neural circuits may mediate phasic and sustained fear. We explored this issue in humans by examining threat predictability in three virtual reality contexts, one in which electric shocks were predictably signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
261
3
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(297 citation statements)
references
References 59 publications
28
261
3
5
Order By: Relevance
“…There is now substantial evidence of BNST activation during evoked anxiety in humans (i.e., from imaging studies [Hasler et al 2007;Straube et al 2007;Somerville et al 2010Somerville et al , 2013Alvarez et al 2011;Yassa et al 2012]), and compelling evidence that electrical stimulation of a brain area lying at the junction of the anterior capsule, anterior commissure, and posterior ventral striatum-an area which corresponds very closely to the area targeted by our cannula-markedly reduces anxiety and depression in patients with otherwise intractable obsessive-compulsive disorder (Greenberg et al 2010). That pharmacological modulation of BNST might also prove therapeutic is an exciting prospect.…”
Section: Discussionmentioning
confidence: 99%
“…There is now substantial evidence of BNST activation during evoked anxiety in humans (i.e., from imaging studies [Hasler et al 2007;Straube et al 2007;Somerville et al 2010Somerville et al , 2013Alvarez et al 2011;Yassa et al 2012]), and compelling evidence that electrical stimulation of a brain area lying at the junction of the anterior capsule, anterior commissure, and posterior ventral striatum-an area which corresponds very closely to the area targeted by our cannula-markedly reduces anxiety and depression in patients with otherwise intractable obsessive-compulsive disorder (Greenberg et al 2010). That pharmacological modulation of BNST might also prove therapeutic is an exciting prospect.…”
Section: Discussionmentioning
confidence: 99%
“…An fMRI study in healthy participants concluded that the BST indexes hypervigilant threat monitoring (Somerville et al, 2010). Another fMRI study in healthy participants found BST activity when comparing unpredictable threat with no threat using virtual reality contexts (Alvarez et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Much of this work uses potentiation of the acoustic startle response as a primary dependent measure 13 , which is the same dependent measure used in the Threat Probability Task. The neurobiological substrates of the startle response circuit have been extensively studied with the discovery of clear connections to the brain structures active in responses to uncertain and certain threats 19,20 . The startle response can be assessed in numerous species which provides a powerful translational tool to study emotions.…”
Section: Translational Research With Animals Using the Startle Responsementioning
confidence: 99%